Regionalism in East Asia the ASEAN + 1 initiatives - Tan, Elizabeth S. (The Philippine Review of Economics, 2008)
Free trade agreements (FTAs) have been proliferating in Asia since the late '90s and show no sign of abating. The ASEAN + 3 model should ideally serve as the starting point because of existing linkages in the real and monetary sectors. Nevertheless, what have emerged are six ASEAN + 1 initiatives. Each of these initiatives covers similar areas of liberalization but progresses at different paces.